Structure, Composition and Diversity of Tree Species at Inobonto Poigar I Production Forest, Forest Management Unit of Poigar, North Sulawesi - Wahyuni, Nurlita Indah Wahyuni; Hendra , Hendra Susanto Mokodompit (Forestry Department, University of Muhammadiyah Makassar, 2016)
Most of primary forest after exploitation era in Indonesia was converted into secondary forest including Forest Management Unit of Poigar. On the other hand the understanding of forest vegetation will help ecology restoration efforts. This study aims to analyze the structure, composition and tree species diversity of Inobonto Poigar I. In order to accomplish the proposed objectives, 31 plots of 20 m x 20 m were randomly established in the forest area where number and name of tree species in each plot was identified and counted. The research was conducted on September 2014 and recorded a total of 78 species within measured plot. The average basal area of the forest was 16,77 m2/ha and the size class distribution was different from primary forest which is resembled a reserved J-shaped pattern. Trema orientalis was found as the dominant species among tree and pole levels, whereas Piper sp. dominated sapling level respectively. The Shannon-Wiener index showed that sapling has the higher diversity than tree and poles. The result of structure and composition analysis of vegetation has indicated that Inobonto I forest is secondary forest.